Influence of Technology Adoption on Operational Performance of Medium Banks During Covid-19 Pandemic in Moshi Municipality, Tanzania - Mosha, Haika Geofrey; Mayala, Nyanjige Mbembela; Onyancha, Hezron (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
Information technology (IT) has transformed the banking industry and the outbreak of the Covid-19 accelerated the trend making the issue of IT adoption more relevant than ever. This study examines the influence of technology adoption on operational performance of medium commercial banks in Moshi Municipality in Tanzania to include Mkombozi Bank, Uchumi Commercial Bank and Akiba Commercial Bank. A concurrent research design with a mixed methods approach was used where utilization of the qualitative and quantitative data was employed. The population of the study was 63 employees of the three banks and the sample size was determined through census technique as the population size was small. Primary data was collected from the respondents while secondary data was collected from the annual report of the year 2019/20 to 2022/2023. For validity of the instrument, face to face and content validity was used while reliability was done through a test-retest process of the instrument. As for data analysis, descriptive statistics, correlation and regression analysis was done to test the influence of technology adoption during COVID 19 pandemic on the operational efficiency of commercial banks in the study area. Findings of the study has shown that debit cards, credit cards, mobile banking and Point of Sale (POS) has positive influence on net profit margin at p-values less than 0.05 while credit cards and debit cards has negative influence on operational efficiency of the studied banks. It is concluded from the study that debit cards, credit cards, internet banking, mobile banking and POS have a positive influence on the net profit margin. Similarly debit cards and credit cards have a negative influence on operating expenses ratio. It is recommended that; banks should take advantage of the technologies to expand their net profit margins while they should be careful with the debit cards and credit cards regarding the operational efficiency of the banks